O efeito da intelig??ncia emocional nas compet??ncias interpessoais do gerente de projetos e no sucesso da gest??o de projetos - Lima, Luiz Fernando (2015)
Emotional intelligence is a relatively recent term, which since its origin is studied in the general workplace. However, in recent years there have been studies focused on emotional intelligence in project environment. In addition, some authors have sought to understand how is the relationship between the interpersonal skills of the project manager, the success of the project management and the level of emotional intelligence of managers. This work aims to identify the relationship between these three themes. For this, we carried out a survey with 119 Brazilian project managers. The data collected were analyzed according to the statistical method of structural equation modeling. The results showed that emotional intelligence and interpersonal skills of the project manager has relevant significance for success in project management. Through the results also can be seen that the influence of emotional intelligence in the success of project management is not direct, but mediated by interpersonal skills of the project manager, when these constructs are analyzed together. These results demonstrate that both, project managers and organizations, should consider these two questions with regard to vocational training for project management activity. Organizations should also take these aspects into account in selecting project managers to its staff as well as the appointment of a manager to a particular project. In theory, also opens up a range for further research with a larger sample, besides incorporating other variables such as type and complexity of the project, operating region, among others. In addition to case studies that provide in-depth analysis of the issue.